1987
DOI: 10.1159/000118371
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Scopolamine: Effects of Single and Repeated Patches upon Psychological Task Performance

Abstract: Scopolamine and placebo transdermal patches were applied on alternating days to 12 normal volunteer subjects. Psychological performance tasks, physiological assessments, a subjective feeling state questionnaire, and a sleep questionnaire were completed each day. Transdermal scopolamine produced significant decrements in memory task performance, daytime feelings of alertness, ease of waking, and alertness following waking, while resting heart rates were lowered. Significant drug × patch number interaction effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…However the task they used had not been demonstrated to be sensitive to psychoactive drug (or other stressor) effects; also the long duration of each stimulus target (20 seconds) was not typical of vigilance measures, where stimulus duration is generally short (Mackworth, 1957). The decreased letter cancellation time in the present study has not been previously reported, since non-significant response time increases have been previously noted (Parrott, 1986a(Parrott, , 1987Parrott and Jones, 1985); although test materials, subject instructions, and test scoring, were constant across these studies. The data were therefore examined for a possible explanation, but none emerged.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…However the task they used had not been demonstrated to be sensitive to psychoactive drug (or other stressor) effects; also the long duration of each stimulus target (20 seconds) was not typical of vigilance measures, where stimulus duration is generally short (Mackworth, 1957). The decreased letter cancellation time in the present study has not been previously reported, since non-significant response time increases have been previously noted (Parrott, 1986a(Parrott, , 1987Parrott and Jones, 1985); although test materials, subject instructions, and test scoring, were constant across these studies. The data were therefore examined for a possible explanation, but none emerged.…”
Section: Discussionsupporting
confidence: 50%
“…With the psychological tests, letter cancellation omission errors were increased, while response times were decreased. The significant increase in omission errors has been reported in each land and sea trial using this measure (Parrott, 1986a(Parrott, , 1987Parrott and Jones, 1985), confirming that sustained attention is impaired with transdermal scopolamine, as it is with oral and parenteral scopolamine (Colquhoun, 1962, Lukomskya andNikolskay, 1971;Parrott, 1986a;Poulton and Edwards, 1974;Warburton, 1983, 1984). These attention decrements have occurred during two laboratory trials where smoking was restricted for 2 hours (30 minutes before testing, and 80-90 minutes during actual testing) (Parrott, I986a, 1987); and during two sea trials where smoking was restricted only during 10 minutes of testing (Parrott and Jones, 1985;present trial).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Tests were selected based on their reported sensitivity to the central effects of cholinergic drugs like physostigmine, donepezil, scopolamine, atropine and caramiphen (Grö n et al, 2005;Levy et al, 1996;McNair et al, 1981;Parrott, 1987Parrott, , 1989Seppä lä and Visakorpi, 1983;Wesnes et al, 1987). Some of the tests were used for the assessment of the effect of rivastigmine in DLB (dementia with Lewy bodies) patients (Wesnes et al, 2002).…”
Section: Cognitive and Emotional Testsmentioning
confidence: 99%